Closing the Gap: A User Study on the Real-world Usefulness of AI-powered Vulnerability Detection & Repair in the IDE - Steenhoek, Benjamin; Sivaraman, Siva; Saldivar, Renata; Mohylevskyy, Yevhen; Zilouchian Moghaddam, Roshanak; Le, Wei (2025 International Conference on Software Engineering, 2025)
Security vulnerabilities impose significant costs on users and organizations. Detecting and addressing these vulnerabilities early is crucial to avoid exploits and reduce development costs. Recent studies have shown that deep learning models can effectively detect security vulnerabilities. Yet, little research explores how to adapt these models from benchmark tests to practical applications, and whether they can be useful in practice. This paper presents the first empirical study of a vulnerability detection and fix tool with professional software developers on real projects that they own. We implemented DeepVulGuard, an IDE-integrated tool based on state-of-the-art detection and fix models, and show that it has promising performance on benchmarks of historic vulnerability data. DeepVulGuard scans code for vulnerabilities (including identifying the vulnerability type and vulnerable region of code), suggests fixes, provides natural- language explanations for alerts and fixes, leveraging chat interfaces. We recruited 17 professional software developers, observed their usage of the tool on their code, and conducted interviews to assess the tool’s usefulness, speed, trust, relevance, and workflow integration. We also gathered detailed qualitative feedback on users’ perceptions and their desired features. Study participants scanned a total of 24 projects, 6.9k files, and over 1.7 million lines of source code, and generated 170 alerts and 50 fix suggestions. We find that although state-of-the-art AI-powered detection and fix tools show promise, they are not yet practical for real-world use due to a high rate of false positives and non-applicable fixes. User feedback reveals several actionable pain points, ranging from incomplete context to lack of customization for the user’s codebase. Additionally, we explore how AI features, including confidence scores, explanations, and chat interaction, can apply to vulnerability detection and fixing. Based on these insights, we offer practical recommendations for evaluating and deploying AI detection and fix models.